2021
DOI: 10.3390/polym13101537
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the LLDPE Constitutive Material Model for Energy Absorption in Impact Applications

Abstract: Current industrial trends bring new challenges in energy absorbing systems. Polymer materials as the traditional packaging materials seem to be promising due to their low weight, structure, and production price. Based on the review, the linear low-density polyethylene (LLDPE) material was identified as the most promising material for absorbing impact energy. The current paper addresses the identification of the material parameters and the development of a constitutive material model to be used in future design… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The nanobag concerns a thin foil (nanofoil) unrolled between side supports. The nanofoil is based on a linear low-density polyethylene (LLDPE), where the material properties were previously identified in both static and dynamic loading conditions [12]. The frontal scenario was chosen as the first step for assessing the performance of the nanobag system due to the ease of comparison to standard airbag performance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nanobag concerns a thin foil (nanofoil) unrolled between side supports. The nanofoil is based on a linear low-density polyethylene (LLDPE), where the material properties were previously identified in both static and dynamic loading conditions [12]. The frontal scenario was chosen as the first step for assessing the performance of the nanobag system due to the ease of comparison to standard airbag performance.…”
Section: Methodsmentioning
confidence: 99%
“…The simplified geometry of the nanobag system was built based on the documentation provided by [6]. The study implements the previously identified linear low density polyethylene LLDPE nanofoil material [12]. Hynčík [12] performed the numerical optimization of material parameters to fit the performed experimental tests.…”
Section: Nanobag Systemmentioning
confidence: 99%
See 1 more Smart Citation